The effectiveness of a program based on cooperative learning - Heba Mohamed Awad (Journal of Architecture, Art & Humanistic Science, 2022)
With the rapid knowledge and technological development, our societies' need has increased for modern teaching mythologies that meet the requirements and needs of the societyOne of the most important factors for the success of university institutions in performing their job to keep pace with global developments is the efficiency of their teachers and students. It is also one of the quality standards to develop the skills of university students to achieve the skills specific to the requirements of the labor market. This is the premise on which the “Cooperative Teaching” program was built as an applied research experiment to link curricula with market needs Work to prepare a qualified graduate who possesses knowledge and skills, and the program is not intended to replace traditional teaching methods with modern methods, but work on two parallel lines, one of which is a traditional one that enhances the student’s learning cognitively and skillfully, and another cooperative that instills the values of participation and cooperation ... in the souls of students.The program was applied to an experimental group of students from the Advertising Department, Faculty of Applied Arts, Damietta University, in the course "Designing Flyers, Flyers, Covers, Correspondence and Calendars" for the academic year (2018-2019), the second semester of the Cooperative Education Strategy, and the course course was chosen to implement the program The proposal is based on the flexibility of the course that is sufficient to include cooperative learning skills and problem-solving skills, which are skills that require learning advanced methods of performance to achieve the objectives of the course.